A study on AM 228 students’ perception on Malaysia general election / Anis Nabila Dolah and Nur Fadzelyni Mohd Ismail - Dolah, Anis Nabila; Mohd Ismail, Nur Fadzelyni (Faculty of Administrative Science and Policy Studies, 2013)
This study had be carried out to identify the major factors that contribute to students’ perception on Malaysia general election among the student from semester 1, semester 3, semester 4, semester 5 and semester 6 Bachelor of Administrative Science (BAS) at UiTM Kampus Bandaraya Melaka. The sample size of population is 104 students. The sampling technique that be used is disproportionate stratified sampling. The main objective of this research are to identify AM 228 students’ general perception on Malaysia general election, to analyze the most contributing factors that affect AM 228 students’ perception on Malaysia general election and to determine the correlation of the factors that influence AM 228 students’ perception on Malaysia general election. The findings indicate, the student attitude/behavior, the leadership quality of candidate, communication channel/publicity and gender becomes factors contribute to the students’ perception on Malaysia general election. This research provides significant information to the students, as a future reference for other studies, also to the UiTM Kampus Bandaraya Melaka administrators and the faculty.